2022
DOI: 10.1186/s12951-022-01467-w
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial of super-stable homogeneous lipiodol-nanoICG formulation-guided precise fluorescent laparoscopic hepatocellular carcinoma resection

Abstract: Background Applying traditional fluorescence navigation technologies in hepatocellular carcinoma is severely restricted by high false-positive rates, variable tumor differentiation, and unstable fluorescence performance. Results In this study, a green, economical and safe nanomedicine formulation technology was developed to construct carrier-free indocyanine green nanoparticles (nanoICG) with a small uniform size and better fluorescent properties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Our previous experimental results showed that SHIFT and ICG was sufficiently stable to protect the fluorescence performance of ICG in vitro. More strikingly, SHIFT and ICG could serve as a good embolic agent and may block the tumor progression of VX2 orthotopic hepatocellular carcinoma models 21–23 . This clinical experiment proved that SHIFT and ICG, like traditional lipiodol, had excellent specific tumor deposition in TAE treatment.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our previous experimental results showed that SHIFT and ICG was sufficiently stable to protect the fluorescence performance of ICG in vitro. More strikingly, SHIFT and ICG could serve as a good embolic agent and may block the tumor progression of VX2 orthotopic hepatocellular carcinoma models 21–23 . This clinical experiment proved that SHIFT and ICG, like traditional lipiodol, had excellent specific tumor deposition in TAE treatment.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, the viscosity of the SHIFT and ICG was comparable to lipiodol and exhibited long-lasting excellent fluorescence navigation in VX2 orthotopic hepatocarcinoma models. 21 To elaborate on the results of the superior performance of SHIFT and ICG previously reported, 22,23 we conducted a clinical application trial. The SHIFT and ICG formulation prepared via SHIFT performs excellent tumor-specific deposition after long-term TAE therapy, which enables ICG to continuously illuminate the tumor regions and microsatellite lesions for specific resection (Figure 1).…”
mentioning
confidence: 99%
“…Our admirable SHIFT nanoICG formulation attracts some surgeon’s attention due to its remarkable and long-time stability and photobleaching resistance of fluorescence and prolonged retention of ICG. A 52-year-old patient with HCC was recruited for the clinical trial of SHIFT nanoICG following ethical approval (Figure a) . After confirming the pathogenetic condition with contrast-enhanced magnetic resonance imaging, SHIFT nanoICG formulation was effectively placed within the primary lesion under the DSA imaging guidance (Figure b).…”
Section: Interventional Fluorescence Image-guided Surgical Navigation...mentioning
confidence: 99%
“…(e–i) Blood AST, ALT, T. Bil, Cre, and WBC values before and 12 days after TAE. Reproduced with permission from ref . Copyright 2022, Wiley Periodicals LLC on behalf of American Institute of Chemical Engineers.…”
Section: Interventional Fluorescence Image-guided Surgical Navigation...mentioning
confidence: 99%
“…In addition, considering that ablation therapy is an invasive local treatment, intratumoral or peritumoral injection may also be a feasible method for nanoparticle delivery. 110,113 A study by Kettering et al found that after intratumoral injection of ultrasmall superparamagnetic iron oxide nanoparticles (USPIOs), most USPIOs remained within the tumor during longterm monitoring, with only a few detected in the liver and spleen, eventually being completely excreted. 199 This indicates that intratumoral injection maximizes the local utilization of nanoparticles.…”
Section: Local Delivery Of Metal Nanoparticles Combined With Ablationmentioning
confidence: 99%